Safeguards to Prevent Neurologic Complications after Epidural Steroid Injections. (May 2015) - Rathmell, James P.; Benzon, Honorio T.; Dreyfuss, Paul; Huntoon, Marc; Wallace, Mark; Baker, Ray; Riew, K. Daniel; Rosenquist, Richard W.; Aprill, Charles; Rost, Natalia S.; Buvanendran, Asokumar; Kreiner, D. Scott; et al.
<x xml:space="preserve">Abstract</x> Background: Epidural corticosteroid injections are a common treatment for radicular pain caused by intervertebral disc herniations, spinal stenosis, and other disorders. Although rare, catastrophic neurologic injuries, including stroke and spinal cord injury, have occurred with these injections. Methods: A collaboration was undertaken between the U.S. Food and Drug Administration Safe Use Initiative, an expert multidisciplinary working group, and 13 specialty stakeholder societies. The goal of this collaboration was to review the existing evidence regarding neurologic complications associated with epidural corticosteroid injections and produce consensus procedural clinical considerations aimed at enhancing the safety of these injections. U.S. Food and Drug Administration Safe Use Initiative representatives helped convene and facilitate meetings without actively participating in the deliberations or decision-making process. Results: Seventeen clinical considerations aimed at improving safety were produced by the stakeholder societies. Specific clinical considerations for performing transforaminal and interlaminar injections, including the use of nonparticulate steroid, anatomic considerations, and use of radiographic guidance are given along with the existing scientific evidence for each clinical consideration. Conclusion: Adherence to specific recommended practices when performing epidural corticosteroid injections should lead to a reduction in the incidence of neurologic injuries.